EFFECTS OF LEVETINOL ON EPILEPTIFORM ACTIVITY OF THE BRAIN IN RATS WITH COBALT-INDUCED EPILEPSY - S. A. Litvinova; T. A. Voronina; L. N. Nerobkova; I. S. Kutepova; G. G. Avakyan; G. N. Avakyan (Эпилепсия и пароксизмальные состояния, 2018)
The aim of this study was to evaluate the anti-seizure effect of Levetinol tablet (Geropharm) on the cobalt-induced chronic epilepsy.Materials and methods. A model of cobalt-induced epilepsy was created by applying cobalt powder to the sensorimotor zone of the rat cortex. The effects of Levetinol were studied at the early stage of the epileptic system (ES) formation (on day 2 after the cobalt application), and then at the stage of fully developed ES (on day 6 after the cobalt application).Results. The present study showed that at the early stage of ES development, Levetinol at doses of 50 and 200 mg/kg had no statistically significant effect on the development of paroxysmal activity in both primary and secondary epileptic foci: in the ipsi- and contralateral cortex, hypothalamus and hippocampus. On day 6 of the cobalt-induced epilepsy, a significant suppression of paroxysmal activity in the above structures of the brain was observed with the administration of Levetinol at a dose of 200 mg/kg. The most pronounced anti-seizure effect was found in the hippocampus; that was expressed in normalization of the bioelectrical activity and appearance of the regular theta rhythm.Conclusion. The effects of Levetinol are largely manifested in the hippocampal foci of epileptiform activity and, to a lesser extent, in the cortical foci.